Young adults' gambling and its association with mental health and substance use problems - Mohammad R. Hayatbakhsh; Alexandra Clavarino; Gail M. Williams; William Bor; Jake M. Najman (Elsevier, 2012)
Abstract Objective: To examine the socio‐demographic characteristics of young adults' gambling and its association with mental health and substance use behaviour. Methods: The study is based on 3,512 young adults (1648 males) for whom data from the Mater‐University of Queensland Study of Pregnancy (MUSP) were available on self‐report gambling, gambling expenditure, Achenbach's Young Adult Self Report and substance use at the 21‐year follow‐up of the MUSP. The participants' age ranged between 18.2 and 23.6 (mean = 20.6, standard deviation = 0.8) years. Results: Two‐fifths of the young adults reported gambling. Males reported more money spent on gambling and were significantly more likely to be at risk of problem gambling. Gambling and problem gambling were significantly more common in less‐educated individuals, those who had higher income or those who had a paid job. Individuals who reported gambling were more likely to smoke cigarettes, drink more than a glass of alcohol per day, use illicit drugs, or exhibit high levels of externalising behaviour than non‐gamblers. Conclusions: The findings confirm the high prevalence of gambling and gambling expenditure in young adults. Individuals who are involved in gambling are more likely to report cigarette smoking, alcohol consumption, and use of illicit drugs. There is a need for further research to explore the mechanisms of association between gambling behaviour and individuals' mental health and substance use. Implications: Substance abuse and mental health services are recommended to consider co‐morbid gambling problems in treatment‐seeking patients.